Typification of the name Stachys recta subsp. tenoreana (Lamiaceae) - Stinca, Adriano; Esposito, Assunta (Phytotaxa, 2019)
Stachys Linnaeus (1753: 580) (Lamiaceae) is a genus composed by annual/perennial herbs and small shrubs, with sessile or short-stalked flowers arranged in axillary clusters on the upper part of the stem forming raceme or spike inflorescences, and very variable calyx that represents an important trait for systematics. It is a subcosmopolitan genus, which includes approximately 370 species (Harley et al. 2004), mainly distributed in the Mediterranean and South-West Asia warm temperate regions.